The Effect of Surgical Treatment on the Quality of Life of Young Women with Breast Asymmetry: A Longitudinal, Cohort Study. Issue 4 (October 2020) - Nuzzi, Laura C.; Firriolo, Joseph M.; Pike, Carolyn M.; Cerrato, Felecia E.; DiVasta, Amy D.; Labow, Brian I.
Abstract : Background: Young women with congenital breast asymmetry have impaired psychological well-being and self-esteem. However, little is known regarding the effects of surgical intervention in this population. This cohort study aims to assess postoperative changes in health-related quality of life following surgical treatment of breast asymmetry in young women using a prospective, longitudinal study design. Methods: From 2008 to 2018, 45 young women undergoing surgical correction of breast asymmetry of benign cause and 101 unaffected, female controls completed the following surveys: Short-Form 36v2, Rosenberg Self-Esteem Scale, and Eating-Attitudes Test-26. Surveys were administered at baseline and at up to 9-year follow-up. Results: Participants with breast asymmetry scored significantly worse than controls at baseline on the Rosenberg Self-Esteem Scale and in two Short-Form 36v2 domains: Social-Functioning and Role-Emotional. Asymmetry participants experienced significant postoperative improvements on the Rosenberg Self-Esteem Scale, and in three Short-Form 36v2 domains: Role-Physical, Social Functioning, and Mental Health. These improvements were sustained for a minimum of 5 years. Postoperatively, asymmetry participants' quality of life was comparable to controls and did not vary by age at the time of surgery, asymmetry severity, or diagnosis. Conclusions: Surgical treatment of breast asymmetry in young women yields significant and sustained improvements in psychosocial quality of life. Postoperatively, patients returned to a level of functioning commensurate with their peers. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.